Understanding factors influencing uptake of healthy lifestyle practices among adults following a community cardiovascular disease prevention programme in Mukono and Buikwe districts in Uganda: A qualitative study - Ndejjo, Rawlance; Musinguzi, Geofrey; Nuwaha, Fred; Bastiaens, Hilde; Wanyenze, Rhoda K. (PloS one, 2022)
Healthy lifestyle practices including physical activity, healthy diets, non-smoking, reduced alcohol consumption and stress reduction are important in the prevention of metabollic CVD risk factors such as hypertension, overweight and obesity, diabetes and hyperlipidaemia. Owing to current lifestyle changes, the increasing burden of CVD and importance of healthy behaviours, the need for strategies to increase uptake of healthy lifestyles among sub-Saharan African populations are apparent. This study explored the factors influencing uptake of healthy lifestyle practices among adults following implementation of a community CVD prevention programme. This was a descriptive qualitative study conducted among purposively selected adults who had engaged in a community CVD prevention programme. Data were collected using in-depth interviews, which were audio recorded and transcribed verbatim. Study transcripts were read into NVIVO 12.6 software for coding and analysis guided by thematic analysis following the semantic approach. This study found variations in uptake of healthy lifestyle practices for CVD prevention with most changes reported for dietary behaviour especially in vegetable and fruit intake, reduction of salt intake and fats and oils consumption. Changes in physical activity were also notable. On the other hand, participants were slow in making changes in alcohol consumption, smoking behaviours and stress reduction. The barriers to uptake of healthy lifestyle practices were individual such as limited capability or skills, structural such as limited physical activity facilities, and social such as cultural and peer influence. Relatedly, the facilitators of practices uptake were individual including knowledge and personal determination to change, and social including social support from family and the community. Insights from understanding the uptake of lifestyle practices should guide planning and design of community programmes with an emphasis on removing barriers and strengthening facilitators building on the intermediate motivating factors and considering individual needs and expectations.